(untitled) (Colombia Medica, 1988)
A group of 104 negroes, 48 men and 56 women, were studied with the presence of abnormal hemoglobins. Sickle cell trait was found in 7.62%; hemoglobin C trait was found in 1.96% of the population. Neither hemoglobin CC nor high fetal hemoglobin nor high A2 hemoglobin were found.